2019
DOI: 10.1002/smll.201805087
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots for In Vivo Bioimaging and Theranostics

Abstract: Carbon dots (CDs), a kind of carbon material discovered accidentally, exhibit unexpected advantages in fluorescence imaging/sensing such as photostability, biocompatibility, and low toxicity. For emerging theranostics, an interdiscipline created by integrating therapy and diagnostics, CDs are good candidates when they are combined with targeted chemo/gene/photodynamic/photothermal therapeutic moieties. Here, the development of CDs in nanomedicine is reviewed from their use as original imaging agents and/or dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
232
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(235 citation statements)
references
References 111 publications
0
232
0
3
Order By: Relevance
“…CDs have been known as novel fluorescent carbon nanomaterials exhibiting sizes below 10 nm. [10] Photoluminescent CDs with ultrastable photoluminescence,e asy preparation, and sustainable raw materials,have been employed in numerous areas including bioimaging, [11] optoelectronics, [12] and photocatalysis. [13] CDs also demonstrate interesting electrochemical redox properties.…”
mentioning
confidence: 99%
“…CDs have been known as novel fluorescent carbon nanomaterials exhibiting sizes below 10 nm. [10] Photoluminescent CDs with ultrastable photoluminescence,e asy preparation, and sustainable raw materials,have been employed in numerous areas including bioimaging, [11] optoelectronics, [12] and photocatalysis. [13] CDs also demonstrate interesting electrochemical redox properties.…”
mentioning
confidence: 99%
“…[7] Carbon dots are commonly applied as both imaging agents and/ or drug carriers, enabling this material a promising multifunctional theranostic system. [8] Furthermore, after being prepared in nanostructures, traditional photo therapy agents show enhanced performance against cancer. Such nanophoto sensitizers provide better efficacy when they are applied in photo dynamic therapy and photothermal therapy.…”
Section: Doi: 101002/smll201902246mentioning
confidence: 99%
“…After the functionalization of target molecules, the lanthanide‐doped nanoparticles are deeply applied in high‐sensitivity biosensing and bioimaging . Carbon dots are commonly applied as both imaging agents and/or drug carriers, enabling this material a promising multi‐functional theranostic system . Furthermore, after being prepared in nanostructures, traditional phototherapy agents show enhanced performance against cancer.…”
mentioning
confidence: 99%
“…Biomolecule‐derived carbon dots (biodots) is a new class of fluorophores that exhibits bright fluorescence with excellent photostability, superb aqueous solubility, and good biocompatibility . In this work, blood‐cell‐selective biodots derived from hydroxyl group containing amino acids (i.e., serine or threonine) are molecularly engineered by adding differently charged polymers into the hydrothermal synthesis to form multifunctional amino acid–polymer biodots for fluorescent blood cell imaging and counting.…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecule-derived carbon dots (biodots) is a new class of fluorophores that exhibits bright fluorescence with excellent photostability, superb aqueous solubility, and good biocompatibility. [8][9][10][11][12][13][14] In this work, blood-cell-selective biodots derived from hydroxyl group containing amino acids (i.e., serine or threonine) are molecularly engineered by adding differently charged polymers into the hydrothermal synthesis to form multifunctional amino acid-polymer biodots for fluorescent blood cell imaging and counting. Particularly, it was found that the polyethylenimine (PEI)-passivated biodots (Type I) can label both RBCs and WBCs, where the fluorescence intensity of labeled WBCs is two orders of magnitude stronger than the RBCs.…”
Section: Introductionmentioning
confidence: 99%